Dampak Kualitas dan Harga Produk Terhadap Kepuasan Konsumen Produk Morinaga Child Kid & Child School Umur 1 – 12 Tahun - Gomies, Stevanus Johan; Amin, Muhamad; Siwabessy, Dominggus J (Journal of Business Application, 2022)
The purpose of this study was to examine and analyze the impact of product quality and price on consumer satisfaction of Morinaga Child Kid & Chid School milk products aged 1-12 years in Ambon City. The population of this study were all consumers of Morinaga Ambon milk products. Sampling using accidental sampling technique with a final sample of 58 respondents. Analysis of research data using Multiple Linear Regression Analysis. The results showed that the variables of product quality and price proved to have a positive and significant effect on consumer satisfaction of Morinaga milk products aged 1-12 years in Ambon City. This can be proven through the regression coefficient of product quality and price which shows that if the value of product quality and price increases, the increase will be followed by an increase in consumer satisfaction for Morinaga Child Kid & Chid School dairy products aged 1-12 years in Ambon City. Thus, it can be said that an increase in product quality and price will increase consumer satisfaction for Morinaga Child Kid & Chid School dairy products aged 1-12 years in Ambon City.